Valve based on novel hydrogels: From synthesis to application - Romero, Marcelo Ricardo (2013)
New hydrogels as materials with potential application in the area of actuators have been developed.Hydrogel synthesis was performed using tris[(hydroxymethyl) methyl]acrylamide (NAT) and itaconicacid (ITA) as monomers and (+)N,N-diallyltartradiamide (DAT) as crosslinker. The hydrogels NAT ITAwere prepared using different molar fraction of monomers and characterized by FTIR-ATR, rheology,swelling properties and mechanical force. The hydrogel prepared with 80% and 20% of NAT and ITA,respectively, has the lowest equilibrium swelling ratio (ESR = 16) in water but the highest elastic modulus(10 ± 1 kPa) and strength (2.2 ± 0.1 N by h). The gel strength increased 0.5 N in a half hour, while the volumeincreased 4 times when passed from an acid medium to a basic medium. This hydrogel was chosen toprepare a pH-sensitive valve to control the flux in a capillary tube. The valve was tested using a systemto control the formation of Fe3+EDTA complex. The response time was 3 and 15 min to open and closethe valve, respectively. The flow of the solution through the valve was 11 L by min. The pressure ofthe solution during the closing of the valve was 10 kPa. The continuous opening and closing of the valveinvolves repetitive expansion and collapse of the network that could damage the structure of the network.However, the valve produced a reproducible and stable response. The dynamic hydrogen bonding existingin the polymeric chains of NAT ITA products could assist in the reversible process when the hydrogelswere subjected to repetitive work. The mechanical properties of the gels and self-healing capacity of thenetworks indicated that the products could be applicable in the development of systems for controlleddrug release.